Reduksi Pemborosan pada Proses Produksi Klem Galah Sawit dengan Pendekatan Lean Manufacturing (Studi Kasus: PT. XYZ) - Kurniawan, Mashur Affandi; Mundari, Siti (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
PT XYZ is a metal manufacturing company that produces various components based on Make to Stock and Make to Order systems. However, the company faces efficiency challenges, particularly on the production line for oil palm pole clamps, where significant time and energy waste leads to customer delivery delays. This study applies the lean manufacturing approach to identify and reduce this waste. Process analysis successfully identified three dominant types of waste: motion, inventory, and waiting, with motion being the largest contributor at 21.66%. Based on these findings, a series of improvements were proposed, including standardized work procedures, 5S implementation, visual management, and operator training. The implementation of these proposals resulted in a 10.55% improvement in total production process efficiency. This gain was achieved entirely by eliminating Non-Value Added (NVA) activities, without altering core Value-Added (VA) processes.